(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Nasolabial Flap remains an under-recognized option for reconstruction of lower lip. We report a successful case of complete lower lip reconstruction after excision of SCC involving most of the lower lip of a 65-year-old male. The surgery was uneventful, and the patient was satisfied with the outcome both functionally and cosmetically at one month follow up. The objective of this report is, to demonstrate the effectiveness of an inferiorly based nasolabial flap for reconstructing a large lower lip defect after squamous cell carcinoma (SCC) excision. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):107-109